A Risk-Based Debt Sustainability Framework : Incorporating Balance Sheets and Uncertainty - Gray, Dale.; Lim, Cheng; Loukoianova, Elena; Malone, Samuel (Washington, D.C. : International Monetary Fund, 2008)
This paper proposes a new framework for the analysis of public sector debt sustainability. The framework uses concepts and methods from modern practice of contingent claims to develop a quantitative risk-based model of sovereign credit risk. The motivation in developing this framework is to provide a clear and workable complement to traditional debt sustainability analysis which-although it has many useful applications-suffers from the inability to measure risk exposures, default probabilities and credit spreads. Importantly, this new framework can be adapted for policy analysis, including debt and reserve management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet